Improving the Attitudes to Homeless Persons in a Family Medicine Residency - Mengyi Zha; Cheri L. Olson; Carol Goulet (SAGE Publishing, 2020)
Introduction: Family medicine providers are at the forefront of serving homeless persons. It is important to prepare family medicine residents for this responsibility during residency. In the current study, we aimed to assess the effect of a series of enrichment activities on the attitudes toward homeless persons held by residents, faculty, and staff in a rural family medicine residency program. Methods: The residency program implemented a 6-month enrichment activities series that provided various educational experiences and aimed to improve the participants' knowledge of and attitudes toward homeless persons. Participants completed 2 anonymous online surveys before and after the enrichment series: (1) the Health Professional's Attitude Toward the Homeless Inventory (HPATHI) and (2) a short survey assessing the understanding of local issues that affected homeless persons. Two-tailed Student t tests were used to compare the survey results. Results: Of the 48 eligible participants, 42 (88%) completed the surveys before enrichment activities and 41 (85%) completed the surveys afterward. Engagement in the enrichment series was associated with a significant improvement in attitudes supporting social advocacy, but it did not affect self-reported levels of cynicism or personal advocacy. Participant knowledge of local homelessness issues improved, but the difference was not statistically significant. Conclusions: The longitudinal enrichment activities series, which was implemented in a rural family medicine residency program and aimed to provide experiences working with homeless individuals, was effective in improving attitudes supporting social advocacy among participants.